2006
DOI: 10.1345/aph.1h077
|View full text |Cite
|
Sign up to set email alerts
|

Bell's Palsy: A Review of Treatment Using Antiviral Agents

Abstract: The use of acyclovir in the treatment of Bell's palsy remains controversial. Additional, adequately powered, randomized, placebo-controlled trials are needed to definitively support its use. For the time being, the evidence reviewed in this article would favor the combination of acyclovir and prednisone if commenced within the first 72 hours of symptom onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…This study described the aetiological factors and prevalence of facial palsy in Kano over a five year period. The findings of this study revealed that the prevalence of facial palsy in this sub-region (9.1%) is relatively higher compared to those previously reported in other sub-regions in Nigeria and other parts of the world (Doner & Kuthuhan, 2000;Grose et al, 2002;Morris et al, 2002;Shmorgun et al, 2002;Alberton & Zed, 2006;Chukwuezi & Nwosu, 2007) who had earlier reported prevalence rates of less than one percent among their study populations. The high prevalence in this study can be attributed to high road traffic accident, higher prevalence of stroke as well as the harsh weather in this region.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…This study described the aetiological factors and prevalence of facial palsy in Kano over a five year period. The findings of this study revealed that the prevalence of facial palsy in this sub-region (9.1%) is relatively higher compared to those previously reported in other sub-regions in Nigeria and other parts of the world (Doner & Kuthuhan, 2000;Grose et al, 2002;Morris et al, 2002;Shmorgun et al, 2002;Alberton & Zed, 2006;Chukwuezi & Nwosu, 2007) who had earlier reported prevalence rates of less than one percent among their study populations. The high prevalence in this study can be attributed to high road traffic accident, higher prevalence of stroke as well as the harsh weather in this region.…”
Section: Discussioncontrasting
confidence: 62%
“…The muscles affected are determined by the type of lesion; infra nuclear lesion affect all the muscles of facial expression while supra nuclear lesion causes weakness of lower two-third part of the facial muscles on the opposite side of the lesion (Grose et al, 2002). The paralysis may include all the muscles and modalities affected by the facial nerve like mimetic facial movement, taste, cutaneous sensation, hearing ability, salivation and drooping on the affected half (Grose et al, 2002;Axellsson et al, 2003;Alberton & Zed, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analyses do have heterogeneity due to differences in antiviral drugs used, drug dosing, and timing of therapy initiation but are nevertheless consistent and unequivocal in their finding of no benefit from antiviral therapy as a singlemodality treatment for Bell's palsy. 2,[70][71][72][73][74] The recommendation against antiviral monotherapy offers the benefit of avoiding the cost and side effects of ineffective antiviral therapy for Bell's palsy. The most commonly observed side effects of antiviral therapy are gastrointestinal related and include nausea, vomiting, and diarrhea, with rare severe reactions, including hives, bronchospasm, angioedema, and hepatic or renal failure.…”
Section: Supporting Textmentioning
confidence: 99%
“…51 When valacyclovir is given in conjunction with prednisone, there is a significant improvement in outcome especially in the elderly than when compared with no treatment at all. 52 According to a recent meta-analysis of prospective, randomized controlled trials, 53 even though the use of antivirals in Bell's palsy remains controversial, the use of acyclovir and prednisone is supported if commenced within the first 72 hours of symptom onset. The 72-hour period of treatment initiation was also supported by a multicenter, randomized, placebo-controlled study 54 that prospectively looked at 221 Bell's palsy patients who were treated with combination therapy within 7 days of symptom onset.…”
Section: Management Of Facial Paralysismentioning
confidence: 99%